Pengaruh Tekanan Stakeholder Dan Board Governance Terhadap Kualitas Laporan Keberlanjutan - Vania Carolina Octora; Muhammad Nuryatno Amin (Owner : Riset dan Jurnal Akuntansi, 2023)
This study investigates the pressure of stakeholders and the governance board on the quality of sustainability reports which are used as the dependent variable. The data used is secondary data obtained from the financial reports of companies in the Basic Materials and Energy Sector which are listed on the Indonesia Stock Exchange (IDX) from 2017 to 2017. 2021. The sample for this study consisted of 14 companies selected using a technique known as purposive sampling. Using multiple linear regression analysis, the relationship between variables was investigated in this study. This research was processed using SPSS version 25. The results of this study, partially Environmental Pressure, Employee Pressure, Consumer Pressure, Investor Pressure, Number of Directors Members, Proportion of Independent Commissioners, and Female Members in Commissioners and Directors have a positive effect while the Age of Members of the Board of Commissioners and Directors has no effect on the Quality of Sustainability Reports in Basic Materials and Energy Sector companies listed on the Indonesia Stock Exchange (IDX) 2017-2021. Simultaneously, all variables have a positive and significant effect on profitability.